Analisa Ekonomi PLTS Off-Grid Dengan Teknologi Pumped Storage Di Mahakam Ulu - Rifqi Fajriyansyah; Irmalia Suryani Faradisa (Journal of Applied Smart Electrical Network and Systems, 2025)
Indonesia continues to face challenges in providing reliable and sustainable electricity, particularly in remote areas that are not yet connected to the main power grid. To support the transition toward clean energy, this study conducts a financial feasibility analysis for the planned development of an Off-Grid Solar Power Plant (PLTS) with Pumped Storage technology located in Batu Dinding, Ujoh Bilang, Long Bagun District, Mahakam Ulu Regency, East Kalimantan. The objective of this research is to evaluate the project’s economic feasibility using financial analysis methods, including calculations of Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit-Cost Ratio (BCR). The study assumes a project lifetime of 50 years with a total investment cost of IDR 99,475,000,000, funded through a government grant. The analysis results show a positive NPV, an IRR of 11.2%, and a BCR of 2.60, indicating that the project is financially viable and profitable. Furthermore, the sensitivity analysis with variations in discount rates (3%–10%) and investment cost increases up to 8% demonstrates that the project remains stable and feasible under different economic conditions. Therefore, the development of the Off-Grid PLTS with Pumped Storage system can serve as a sustainable and clean energy solution for electricity supply in remote regions of Indonesia.